Pivot subtitling : reasons and results in the Korean-Turkish context - Dallı, Harun. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The present thesis undertakes a comprehensive investigation of pivot subtitling (i.e., indirect subtitle translation) within the Korean-Turkish context. Pivot subtitling is a natural outgrowth of the dynamic and globalizing mediascape, and it is essential to comprehend the function of pivot templates in the worldwide dissemination of local and non-English content in order to establish a robust theoretical foundation for the practice. As a vital component of current audiovisual translation (AVT) methods, pivot subtitling is not simply a response to purported shortages in qualified linguists capable of translating directly between particular language combinations, but rather a deliberate policy and strategy pursued by streaming services and their vendors to centralize multi-language subtitling workflows via a single mediating language. The study demonstrates that the Turkish subtitling of Korean content on Netflix is contingent upon indirect translation via pivot templates, and that Turkish subtitlers are disincentivized, if not outright prohibited, from deviating from pivot templates. The dissertation endeavors to explore a methodological and theoretical framework for the identification and investigation of pivot subtitles, with the ultimate objective of fostering future research in this field. Through a qualitative examination of the Turkish pivot subtitles of Parasite (Bong, 2019b), the study brings attention to the translational ramifications of repurposing commercially available subtitles as pivot templates for second translations. Overall, this thesis offers informed insights for industry stakeholders and translation scholars, and promotes the refinement of existing workflows through a theoretical framework.
Keywords: Netflix (Firm); Korean language -- Translations into Turkish..